Tissue Factor mRNA Quantitation without Prior Monocyte Isolation. (June 2000) - Javorschi, Sandrine; Labrouche, Sylvie; Freyburger, Genviève
Monocyte tissue factor (TF) quantitation evaluates the involvement of coagulation processes in many diseases. However, technical difficulties, such as blood sampling of cells representative of the whole intravascular pool, cell isolation, protein quantitation or activity assessment, hinder reliable evaluation of TF expression by activated monocytes. Early determination of such activation can be achieved through TF mRNA quantitation by RT-PCR and sensitive product detection, such as automated electrophoresis of fluorescently labeled products. Although it is very sensitive, this method has its limitations. It needs to be standardized using other mRNA that display two main characteristics: the absence of upregulation during inflammation and similar levels of expression when compared with the target mRNA. Widely used standardization housekeeping genes such as HLA or GAPDH genes only meet the former reproducts. Although it is very sensitive, this method has its limitations. It needs to be standardized using other mRNA that display two main characteristics: the absence of upregulation during inflammation and similar levels of expression when compared with the target mRNA. Widely used standardization housekeeping genes such as HLA or GAPDH genes only meet the former requirement. We demonstrate here that CD11b gene expression meets both conditions. Moreover, because of its specific expression in myelomonocytic cells, it is possible to avoid further monocyte purification from a regular mononuclear cell preparation. A rapid, sensitive, specific and accurate way to evaluate monocyte TF expression is described in this paper.